Rule Based Planning for Solving Hanoi Problem - safwan hasoon (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this research, the planning intelligence technique has been developed and applied to solve the tower  of Hanoi puzzle through the construction of the rule based included a set of facts and rules under certain conditions to describe this problem. The tower problem of Hanoi consists of different size disks and three pegs. The proposed system is to transfer the disks from the initial state to the goal state by using some rules. The rule based is used from planning to get the goal by applying different operations. The intelligence techniques used are contributed to reduce time and memory (state space) compared with traditional planning depended on human aid which spends more time and memory, since this technique solved a problem in the depended are planning the approach without human aid. The prolog language is used to implement the computer simulation program for the proposed system.